PLAGIARISM IN MODERN EDUCATION: A PROBLEM OR A SYMPTOM? - Dmitry A. Sevostyanov (Высшее образование в России)
The article analyzes the causes of academic plagiarism in modern education. It is shown that the distribution of academic plagiarism is a symptom of the mismatch between the existing traditions in education and the tendencies of postmodernism. It is also shown that the problem of plagiarism cannot be solved within the framework of this problem. The analysis of inversions in hierarchical systems allows to identify the causes of the prevalence of plagiarism. Inversion is an internal contradiction in the hierarchy between the position of the hierarchical element and its role. The reason for inversions is the discrepancy between the orientation of the organizational principles of hierarchy. The development of inverse relationships in the system leads to the destruction or radical transformation. The current situation in education is due to the inverse relationship in the system of human activity that precedes a leap in its development. In these circumstances, combating plagiarism should be based on significant changes in the formation and deletion of obsolete academic traditions.